The Assessment of Effective Strategic Management Taxonomy in Reformulating Efficient Modern Management Disciplines for Promoting Organizational Growth and Development of Corporate Organizations in Thailand - Vongsurakrai , Suwanna (Digital Repository of Theses, 2024)
This doctoral dissertation presents a practical examination of the quantitative impact of a strategic management taxonomy on the growth and development of Thai corporate organizations. By incorporating quantitative analysis, this research aims to provide a pragmatic perspective on the application of strategic management taxonomy within the context of organizational growth. The research delves into the specific variables that contribute to successful implementation and integration, while considering the unique challenges posed by the dynamic business environment in Thailand. The primary objective of this study is to assess the effectiveness of a strategic management taxonomy as a powerful tool for reshaping contemporary management practices, thereby fostering long-term growth and success. By conducting a comprehensive quantitative analysis, the research seeks to validate the applicability and influence of the strategic management taxonomy. This is achieved through the thorough examination of case studies and empirical data, offering actionable insights that can lead to the refinement and practical implementation of the strategic management framework within enterprises. Focusing on the distinct landscape of the Thai business environment, characterized by cultural nuances, regulatory frameworks, industry dynamics, and market conditions, this study intends to provide context-specific insights. It acknowledges the multifaceted challenges that organizations face in today's rapidly evolving business landscape, encompassing technological advancements, shifting customer expectations, global competition, and market dynamics. With this backdrop, the strategic management taxonomy assumes pivotal importance in aligning objectives, resources, and capabilities with the external environment. The research methodology comprises a multidimensional approach, combining case study analysis, surveys, interviews, and data analysis. The study evaluates existing strategic management strategies employed by Thai corporations, identifying strengths and weaknesses. It systematically gathers relevant data on strategic management processes, implementation strategies, and performance outcomes. The collected data undergoes rigorous statistical analysis, utilizing techniques such as descriptive statistics, correlation 5 analysis, and regression analysis. Within this analytical framework, the study investigates the influence of corporate culture, leadership support, employee engagement, and change management strategies on the successful deployment and integration of the strategic management taxonomy. By dissecting these independent variables, the research aims to identify their respective impacts on organizational outcomes, thereby offering actionable insights for improved decision-making and resource coordination. In conclusion, this dissertation offers a quantitative exploration of the strategic management taxonomy's role in reshaping modern management practices to drive the growth and development of Thai business organizations. The study bridges the gap between theory and practice by systematically evaluating the taxonomy's impact, aligning it with the unique challenges of the Thai business environment. The research contributes to the existing body of knowledge on strategic management and provides practical guidance for organizations seeking sustained growth and success in today's dynamic business landscapes.